Effect of Radiofrequency on DNA Damage and Oxidative Status in Patients with Turbinate Hypertrophy. - ŞENTÜRK, EROL; Tugrul, S; TUĞRUL, SELAHATTİN; Koçyiğit, A; DOĞAN, REMZI; Senturk, E; EREN, SABRİ BAKİ; Doğan, Remzi; ÖZTURAN, ORHAN; Eren, SB; KOÇYİĞİT, ABDÜRRAHİM; Ozturan, ORHAN; et al. (My University, 2019)
The radiofrequency devices that are used generate radiofrequency in the frequency range of 1.5 and 2.5 MHz. This study aims to demonstrate whether systematic oxidative status and DNA are influenced in this frequency range. In study, 27 patients who received radiofrequency treatment on inferior turbinate as they were diagnosed with inferior turbinate hypertrophy. DNA damage was assessed by alkaline comet assay in peripheral lymphocyte cells. Plasma levels of total antioxidant status (TAS), total oxidative status (TOS) were determined by using an automated measurement method and oxidative stress index (OSI) was calculated (OSI was calculated as: OSI = (TOS/TAS) × 100). There were increased in the OSI and TOS values on days 1 and 15 as compared to the samples taken before the radiofrequency administration. Significant decreases were seen in TAS values on days 1 and 15. As for the DNA damage, no significant differences were found on day 15 compared to the preoperative values even though there was a statistically insignificant increase on day 1. Administration of radiofrequency radiation on inferior turbinates results in increased oxidative stress in the acute period and a decrease in the anti-oxidative system. Although this effect causes a slight increase in the DNA damage in the early post-operative period, the damage is restored to the pre-operative levels on day 15. Therefore, we believe that a more conservative approach should be selected for radiofrequency treatment instead of using it routinely.
Keywords: Radiofrequency radiation; Oxidative stress